Spread of Mink SARS-CoV-2 Variants in Humans: A Model of Sarbecovirus Interspecies Evolution - Devaux, Christian A.; Pinault, Lucile; Delerce, Jérémy; Raoult, Didier; Levasseur, Anthony; Frutos, Roger (Frontiers in Microbiology, 2021)
While proceeding with the vaccination of populations against SARS-CoV-2, a concern has emerged regarding the rapid spread of viral variants and the fear that some of them escape vaccine protection. These variants result from selective sweeps in both humans and animals who are susceptible to SARS-CoV-2. Some of these variants were diagnosed in humans after spreading through densely caged minks. The claim that these variants exhibited lower susceptibility to neutralization by antibodies led the Danish government to order the slaughter of 17 million minks. Since then, SARS-CoV-2 prevalence tests have led to the discovery of other infected minks worldwide. In this study, we revisit the issue of the circulation of SARS-CoV-2 variants in minks as a model of sarbecovirus interspecies evolution by: i) comparing the human and mink ACE2 and NRP-1 receptors; ii) comparing SARS-CoV-2 in humans and minks; iii) analyzing the impact of mutations in the three-dimensional structure of the spike engaged with the ACE2 receptor; and iv) predicting the linear epitopes target for immune response. Although mink-selected SARS-CoV-2 variants which carry the Y453F/D614G mutations display an increased affinity for human ACE2 and can escape neutralization by one monoclonal antibody, they are unlikely to lose most major epitopes predicted to be targets for neutralizing antibodies. We discuss the implications of these results for the rational use of SARS-CoV-2 vaccines.